The Effect of Husband Support on the Successful Initiation of Early Breastfeeding in the Work Area of Pakisjaya Public Health, Karawang Regency In 2022 - Dinda Aulia; Mariyani Mariyani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The success of breastfeeding in a group of husbands who understand breastfeeding. Methods:  This study employed a cross-sectional, analytical survey research strategy. A total of 32 participants were randomly selected for the sample. Both univariate analysis and bivariate analysis utilizing the Chi-Square test were performed on the data. Results:  According to the study's findings, the proportion of husbands who are extremely supportive of early breastfeeding is 62.5% greater than the number of husbands who are less supportive of early breastfeeding is 6.3%. The statistical test findings revealed that there was a substantial influence on the husband's support for the success of Early Breastfeeding (p-value 0.038 0.05). This suggests that the husband's support is linked to the success of the Early Breastfeeding Intervention. Conclusion: There is an effect of the husband's support on the success of early breastfeeding initiation in the work area of ​​the Pakisjaya Public Health Center, Karawang Regency in 2022.